Effect of diet during larval development of Menippe nodifrons Stimpson, 1859 and Callinectes danae Smith, 1869 - Guarizo, Matheus [UNESP]; Costa, Tânia Marcia [UNESP]; Marochi, Murilo Zanetti [UNESP] (Springer Nature, 2020)
The worldwide decrease in fishery stocks in recent years is related to the degradation of coastal environments and to the increases in capture effort and extreme natural events. Restocking dilapidated populations with artificial hatchery-reared larvae has arisen in recent years as a viable technique for the reparation and maintenance of stocks of commercially exploited species. One of the first steps in larvae cultivation is the evaluation of an appropriate diet for rearing. We aimed to test viable diets for feeding zoea larvae of the crab Menippe nodifrons and the swimming crab Callinectes danae. We tested five live food treatments, three microalgae (Tetraselmis gracilis, Chaetoceros calcitrans, and Thalassiosira weissflogii), the rotifer Brachionus plicatilis, and Artemia sp. nauplii. The most suitable feeding protocol for rearing M. nodifrons larvae was a combined diet of enriched B. plicatilis up to the zoea III instar with the introduction of hatched Artemia sp. nauplii onwards to the megalopa stage. Larvae of C. danae showed high mortality rates and none achieved the zoea III phase on any of the diets tested. Although our results for C. danae rearing were not conclusive, the data provide additional information on improper rearing diets for this species for future research. Future studies testing other food sources are necessary to improve larvae production.
Keywords: Brachyura; Fishery stocks; Food organisms; Larval survival; Microalgae